Hypertension Control at the Primary Health Care: A Comparison Among Portuguese Natives and Portuguese Speaking African Coutries Immigrants - Lopes, Elisa (2016)
Introduction: In Portugal, the frequency of patient with treated and controlled hypertension is low. It is unknown the relation of socio-economic determinants with hypertension control, particularly in African immigrants. Aims: To compare frequency of control in treated hypertension and to identify characteristics associated with uncontrolled and treated hypertension between Portuguese natives (Caucasian) and Portuguese Speaking African Coutries immigrants (black). Material and Methods: Cross-sectional study of patients with treated hypertension, 40-80 years old, randomized from Primary Health Care of Lisbon Region. We collected sociodemographic, clinical and health care data through structured interviews. We compared the frequency of patients with uncontrolled hypertension, and identified related factors through univariate and multivariate analysis. Results: In this study participated 786 patients with treated hypertension (participation rate: 71%): 449 natives and 337 immigrants. Of these, 46% had controlled hypertension. Diastolic blood pressure was higher in younger immigrants. Were associated with no control, in natives, male sex, low education, going to emergency and / or nursing services and not looking for the family doctor; on immigrants, being single, using the pharmacist, the number of years of illness and intentional non-adherence.Discussion: Treated hypertension control has been increasing for last years. Natives and immigrants differ, regarding blood pressure control, relatively to the frequency of family doctor consultation, and resorting to other services and health professionals. These differences didn´t reflect in statistically different control rates.Conclusions: It is needed to define strategies to control hypertension in primary health care specific for ethnic groups.